Effect of Austenitizing and Tempering on Impact Resistance of a Hot Rolled High Strength Steel - Lieth, Haider Mahdi; Hammood, Ali Sabea (Basrah Journal for Engineering Sciences, 2021)
The aim of this study is to investigate the effect of heat treatments on the impact properties of hot rolled high strength steel and describes the effect of tempering temperature and quenching media on the microstructure, hardness, and impact resistance of plates. In the present study a high strength steel was austenitized at 900 °C with different quenching medium and followed by tempering at 300 °C, 500 °C. After thermal treatments, the values of Charpy impact resistance, hardness, and microscopic structure were evaluated from mechanical and metallographic analysis of metals respectively. The change of mechanical properties and microstructure of the metal with the existence of heat treatment with the ballistic performance of high-strength steel. Experimental results showed that tempering at 500 °C for 2 hours after water quenching medium it provides the best mechanical properties in conjunct on with an improved in microstructure.